BIMBINGAN KELOMPOK MASYARAKAT DESA MENURAN KECAMATAN BAKI DALAM PEMBANGUNAN DAN PENGEMBANGAN POTENSI WISATA DI SUNGAI BAKI - Kurniawan Kurniawan; Elvina Dwi Anita; Syahna Utami Nisa (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2020)
This program aims to help the Menuran Village community in the development and development of tourism potential in the river tray, Menuran Village is a group of people who are able to interact and work together in empowering existing potential so as to be able to make innovations as a tourist village, use and use of land as a tourist village location in Baki Subdistrict, Sukoharjo Regency needs to be improved. The problem faced by the community at this time is the lack of training in the use of technology, improvement of facilities and infrastructure around the site. Therefore it is necessary to conduct training and group guidance in developing tourism potential in the Baki River. To achieve this goal the method used is socialization and training and improvement of facilities and infrastructure in the form of health sanitation facilities and the provision of tourist boats. The result of this activity is the formation of a river tourism village in Menuran, in addition partners also have more knowledge in the world of tourism and the community is more creative in managing the potential of the river as an educational tourist attraction. The results of this activity also formed the river tourism village so that it can be used as income for the community in meeting their daily needs and for the community to always maintain and maintain the river to look more beautiful.